The Dilemmas Associated whit the Introduction of Performance Budgeting in Local Government - Korczakowski , Dariusz (Studia Oeconomica Posnaniensia, 2013)
Performance budgeting is presented as a remedy for the financial problems in the public finance sector. This is being considered for implementation in Polish local government units. According to the author of the article there is no justification, at the moment, for the introduction of performance budgeting in local governments; doing so by force will have the opposite effect - lower efficiency (higher employment) and increased bureaucracy. This is due to its novelty and the lack of uniform standards in the methodology of performance budgeting. Also, national and foreign experience does not support the full effectiveness of this tool. In particular, selecting appropriate measures and indicators relating to the implementation of the planned tasks can be difficult. The current legal status does not help either: the performance budgeting which is being introduced now functions as a parallel budget. Nevertheless, it seems reasonable to implement elements of performance budgeting, if only because of its presentation function which will help to better understand the enormity of the tasks performed by local governments, but it ought to be done on a voluntary basis.